Structural, optical, magnetic and thermal investigations on Cr3þ ions doped ZnS nanocrystals by co-precipitation method - Basha, Sk. Johny (Elsevier, 2019)
Cr3þ ions doped ZnS nanocrystals were synthesized using the co-precipitation method. The as-prepared sample was characterized to investigate the magnetic and thermal properties along with its structural and spectral studies. X-ray diffraction (XRD) analysis confirms the cubic zinc blend structure, and the mean crystallite size is evaluated to be 4.7 nm. Scanning electron microscope (SEM) and transmission electron microscopy (TEM) images indicate stone-like structures. The deposition of Cr3þ ions in ZnS nanocrystals is evidenced by energy dispersive spectroscopy (EDS) analysis. From the optical absorption data, the bands in the UV-VIS region are recognized as the characteristic bands of Cr3þ ions. Crystal field and Racah parameters are calculated as Dq ¼ 1564, B ¼ 567 and C ¼ 3389 cm 1. The electron paramagnetic resonance (EPR) spectrum exhibits well resolved paramagnetic resonance signal at g ¼ 1.982 which arises from the exchange interaction between Cr3þ ions. It reveals from the correlating optical and EPR results that the Cr3þ ions occupy distorted octahedral site symmetry in the host lattice. Photoluminescence spectrum shows three distinct emission bands in blue, green and orange regions. Commission International de I'Eclairage (CIE) chromaticity coordinates are found in the blue region at (x, y) ¼ (0.172, 0.121). In addition, the prepared nanocrystals exhibit a ferromagnetic behavior with a coercive field (Hc) of 513 Oe. The thermal steadiness of the prepared samples was characterized by Thermal gravimetric e Differential thermal analysis (TG-DTA). These Cr3þ ions doped ZnS nanocrystals find potential applications in LEDs, spintronics and nanoscale quantum devices